Review: Bedae Presbyteri expositio Apocalypseos - Ward, Benedicta (The journal of theological studies, 2003)
Bedae Presbyteri expositio Apocalypseos Roger Gryson 606 Turnhout (Corpus Christianorum Series Latina, 121A.) Brepols 2001 Hardback€249 2 503 01213 2 Paperback€237 2 503 01214 o